2012
DOI: 10.1016/j.mambio.2011.11.007
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the taxonomy and phylogeny of social voles inferred from mitochondrial cytochrome b sequences

Abstract: a b s t r a c tWe sequenced the entire cytochrome b gene in Microtus paradoxus from Turkmenistan and Microtus socialis from Crimea and Kalmykia. Phylogenetic relationships among social voles were reconstructed by the inclusion into analyses of a further 23 published haplotypes belonging to six species. The two probabilistic methods which were used in phylogenetic analyses, the Bayesian inference and Maximum Likelihood, yielded very similar results. Both trees showed two highly divergent lineages which were fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…The resulting tree depicting the relationships between species cannot be directly compared to available molecular trees because different species were employed in individual analyses (Jaarola et al, 2004;Kryštufek et al, 2012;Martínková and Moravec, 2012). However, the close relationships between M. irani and M. schidlovskii were also supported in the tree proposed by Zorenko et al (2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting tree depicting the relationships between species cannot be directly compared to available molecular trees because different species were employed in individual analyses (Jaarola et al, 2004;Kryštufek et al, 2012;Martínková and Moravec, 2012). However, the close relationships between M. irani and M. schidlovskii were also supported in the tree proposed by Zorenko et al (2014).…”
Section: Discussionmentioning
confidence: 99%
“…Musser and Carleton (2005) recognized eight species in this group but this treatment has been under intensive discussion. Kryštufek et al (2009Kryštufek et al ( , 2012 and Zorenko et al (2014) distinguished two basic phylogenetic branches within this group, i.e. the socialis and the guentheri lineages.…”
Section: Introductionmentioning
confidence: 99%
“…The senior author considers it as an independent species, proving the opinion by data on the molecular and genetic analysis on a gene cytochrome b, partial sterility of hybrids from crossing of this form with Microtus socialis (Zykov & Zagorodnyuk, 1988;Kryštufek et al, 2012;Zorenko, 2012) and morphology of body and brain (Zorenko, 2013). The junior author considers the Kopet Dag vole as a subspecies M. s. paradoxus.…”
Section: Introductionmentioning
confidence: 92%
“…Kryštufek et al (2012), in an analysis of voles (Microtus) based on cytochrome b sequences, found divergence levels within two acknowledged species that exceeded the threshold of 4.3%, a conservative cut-off criterion between sibling species in Microtus. A similar line of reasoning led Osmers et al (2012) to support the separation of southern and eastern oryx antelopes (Oryx gazella and O. beisa).…”
Section: Potential Guidelines and Concluding Remarksmentioning
confidence: 99%